Florida Peach and Nectarine Varieties - Mercy Olmstead; Jose Chaparro; Pete Andersen; Jeff Williamson; James Ferguson (EDIS)
The University of Florida has developed high-quality, low-chilling, early maturing peach and nectarine cultivars that can be grown from the panhandle of Florida to as far south as Immokalee. Low-chilling cultivars can grow and produce fruit under Florida conditions that are much warmer in winter than in northern states. Furthermore, ripening of these cultivars during April and May ensures an early spring market window for tree-ripe fresh fruit in Florida before peaches and nectarines from other southeastern states and California come to market. Both commercial and dooryard recommended varieties span the growing season. This 8-page fact sheet was written by Mercy Olmstead, Jose Chaparro, Pete Andersen, Jeff Williamson, and James Ferguson, and published by the UF Department of Horticultural Sciences, May 2013.